PELAKSANAAN PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SEKOLAH MENENGAH KEJURUAN - Ary Kurniawan; Fitri Nur Mahmudah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
The learning process is inseperable from the application of information and communication technology in order to maintain the quality of learning. This study aims to describe the implementation of information and communication technology-based learning in the Fine Arts Expertise Program at Vocational Senior High School (Sekolah Menengah Kejuruan/SMK Negeri 5 Yogyakarta. This research use qualitative approach with case study. Data collection is taken through observation, interviews, and documentation. Data were analyzed qualitatively using the interactive analysis techniques of the Miles and Huberman models with the steps of data collection, data reduction, data display and conclution / verification. The data validity technique is triangulation technique. The results figured out that the Fine Arts Expertise Program at SMK Negeri 5 Yogyakarta had implemented Information and Communication Technology (ICT) based learning using multimedia presentations, computer equipment, laptops and LCD projectors, and learning resources from the internet.